2018
DOI: 10.1016/j.exer.2018.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Posterior stromal cell apoptosis triggered by mechanical endothelial injury and basement membrane component nidogen-1 production in the cornea

Abstract: This study was performed to determine whether cells in the posterior stroma undergo apoptosis in response to endothelial cell injury and to determine whether basement membrane component nidogen-1 was present in the cornea. New Zealand White rabbits had an olive tip cannula inserted into the anterior chamber to mechanically injure corneal endothelial cells over an 8 mm diameter area of central cornea with minimal injury to Descemet's membrane. At 1 h (6 rabbits) and 4 h (6 rabbits) after injury, three corneas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 19 publications
2
22
0
2
Order By: Relevance
“…Posterior fibrosis does not occur if the endothelium alone is removed over an 8-mm-diameter circle using an olive tip cannula, despite apoptosis of the overlying posterior stromal keratocytes and the ensuing stromal wound healing response. 77 This experiment confirms that Descemet's BM is the critical modulator of posterior corneal fibrosis, as the EBM is for anterior corneal fibrosis. Further study is needed to fully understand the role Descemet's BM plays in the modulation of posterior corneal fibrosis that occurs after corneal infections, diseases, trauma, and surgeries.…”
Section: Posterior Corneal Fibrosissupporting
confidence: 67%
“…Posterior fibrosis does not occur if the endothelium alone is removed over an 8-mm-diameter circle using an olive tip cannula, despite apoptosis of the overlying posterior stromal keratocytes and the ensuing stromal wound healing response. 77 This experiment confirms that Descemet's BM is the critical modulator of posterior corneal fibrosis, as the EBM is for anterior corneal fibrosis. Further study is needed to fully understand the role Descemet's BM plays in the modulation of posterior corneal fibrosis that occurs after corneal infections, diseases, trauma, and surgeries.…”
Section: Posterior Corneal Fibrosissupporting
confidence: 67%
“…It is worth noting that transplanted Fresh-RCECs contributed to prevent such changes in the corneal stroma. It has also been reported that mechanical corneal endothelial injury in rabbits triggers apoptosis of posterior stromal cells in the short term 41 . Further studies are required elucidate how cell apoptosis and fibroblastic cells affects wound healing in the long term.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, recent evidence suggests that a posterior wound healing response is triggered upon disruption of the corneal endothelium. 90 This could potentially cause fibrosis to form in the posterior stroma, which would confound assessment of anterior stromal haze. In the present study, fibrosis was limited to the anterior-to midstroma in all wounded corneas, based on slit-lamp examination and post hoc immunofluorescent microscopic evaluation.…”
Section: Discussionmentioning
confidence: 99%